On the Making and Breaking of Social Music Improvisation during the COVID-19 Pandemic - Cai, Carrie J.; Terry, Michael (2020)
ABSTRACT Music improvisation has traditionally been a real-time, collocated group activity where individuals listen and react to one another as they organically create music together. The severe restrictions of COVID-19 provide an extreme case study of how remote work is affecting music improvisation practices, and how technology might co-evolve to better support those creative needs. We report results from interviews of six professional music improvisation artists during the pandemic. We found that, despite modern remote communication technologies, remote work has had a detrimental impact on musicians’ livelihood and practice. The inability to make music with others in real-time has erected barriers to creative music production, and made it challenging to create “safe spaces” for the creative process. In response, new forms of social practices have begun to emerge, including increased use of elongated spaces and silences to facilitate remote music making sessions, new types of large-scale distributed music-making, and global, societal dialogues about music. Author Keywords Creativity; Music; Remote Collaboration; Remote Work ABOUT THE AUTHOR/S Carrie J. Cai Google Research cjcai@google.com Carrie Cai is a Senior Research Scientist at Google Brain and part of the People+AI Research (PAIR) Initiative. Her research aims to make human-AI interactions more productive and enjoyable to end-users, ranging from doctors diagnosing cancer with the help of AI assistants, to everyday people co-creating music and art with AI. Her work has been adopted into ML-powered systems at Google Health, and has also received 4 best paper/honorable mention awards. https://sites.google.com/view/carriecai/ Michael Terry Google Research michaelterry@google.com New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).